'Rules about rules' and the endogenous dynamics of international law: Dissonance reduction as a mechanism of secondary rule-making - Theresa Reinold; Michael Zürn (Global Constitutionalism, 2014)
We can observe some developments that indicate a further strengthening of human rights and the rule of law even after 2001. These developments are puzzling as they occurred despite largely unfavourable scope conditions. This article offers an account of these developments that focuses on dynamics endogenous to the law. These internal dynamics provide a causal mechanism that sets in once a certain threshold of legalization has been reached. We employ the Hartian notion of secondary rules which we think is an especially helpful conceptual tool to analyse the endogenous dynamics of legal systems. To the extent that law is programmed towards consistency, secondary rules become necessary in an environment of rapidly increasing legal density to govern the complexity resulting from this proliferation of norms. Upholding consistency is necessary to maintain the autonomy of law in a Luhmannian sense and the `morality' of the legal system in a Fullerian sense. Our goal is to show this and at the same move beyond an argument of system or normative functionality by identifying causal mechanisms that can explain the law's built-in drive towards secondary rules, and that are in accordance with broader social science theory. We use some insights from cognitive psychology to develop these causal mechanisms further. While testing these causal mechanisms would be beyond the scope of this paper, we hope to provide the conceptual tools for future empirical research on the dynamics of secondary rule-making and offer some empirical illustrations to demonstrate how dissonance reduction operates in practice.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation).
Keywords: 330; cognitive mechanisms; dissonance reduction; endogenous dynamics of legal systems; legal consistence; secondary rules